Control of rapid phase oscillations in the modelling of large wave energy arrays. (September 2015) - Isberg, J.; Engström, J.; Eriksson, M.; Göteman, M.
Highlights: Method for simulating large wave converter arrays with full hydrodynamical interaction. Mitigating the problem of rapid phase oscillations appearing in numerical simulations. This is done by analytically integrating out the factors that are causing the oscillations. We have successfully utilized this method to model parks with up to 1000 point absorbers. Abstract: Several recently developed concepts for economically viable conversion of ocean wave energy are based on large arrays of point absorbers. Simulations of the hydrodynamic interactions between devices in wave energy parks provide guidelines for optimal configurations with regard to maximizing produced electricity while minimizing fluctuations and costs. Parameters that influence the performance include the geometrical lay-out of the park, the number of wave energy converters and their dimensions and separating distance, as well as the wave climate and the incoming wave spectral characteristics. However, the complexity of the simulations increases rapidly with growing number of interacting units, and simulations become a severe challenge that calls for new methods. Here we address the problem of rapid phase oscillations appearing in the simulation of large arrays of point absorbers using potential theory for the structure–fluid interaction. We do this by analytically integrating out the factors that are causing the oscillations. Our group has successfully utilized this method to model parks with up to 1000 point absorbers.